4x – 9y = 7–2x + 3y = 4What number would you multiply the second equation by in order to eliminate the x-terms when adding to the first equation?

Accepted Solution

Answer:By 2.Step-by-step explanation:You need to eliminated the x-terms, so the first step is to focus only in those terms.So yo have 4x and -2x, since you are thinking in eliminate then you have this equation> [tex]4-2*K=0[/tex]Note that we dont put the x variable, since we are studying its coefficients in the equations system.Solving for K, Gives us that K=2So.Multiplying the second equation by 2 results in[tex]-4x+6y=8[/tex]When you put them together, it gives you the following[tex]4x-9y -4x+6y- 7+8[/tex]and the final equation is[tex]-3y=15\\[/tex]giving you the answer for y, that is [tex]y=-5[/tex]